6 Sigma and DMAIC Method: Basic Tool Teaching and Application for Beginning Practitioners in Automotive Assembly - Baro, Manuel; Piña Monarrez, Manuel Román; Reyes, Aida Yarira (2023)
The 6 Sigma methodology is widely used in different types of industries, from manufacturing type industries to service industries. The objective of the methodology is based on reducing variability in the production system, that is, achieving that the standard deviation is as many times as possible within the mean of the process being measured. The Six Sigma methodology is based on the DMAIC process which is to define, measure, analyze, implement, and control, with these stages, it is possible to identify quality critics and understand their root cause, therefore, if it is known Why a problem occurs, it can be fixed. With DMAIC methodology, the reduction of the variation that arises from the types of problems that were mentioned within the 6 Sigma methodology is sought. In the other hand, 6 sigma and DMAIC process possess more that 40 quality tools to improve the critical of quality and in these manners increase the company efficiency. In such a way, the objective of this research is the presentation of the most effective tools and simply to apply in companies of the methodology, also how this quality tools can be applied in any type of problem to increase efficiency and productivity, this with the necessity of companies’ quality improvement and beginners’ practitioners can used as a simple way of the methodology implementation.